2012
DOI: 10.1108/10444061211267290
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a mediation program in symmetrical versus asymmetrical neighbor‐to‐neighbor conflicts

Abstract: Purpose -The last decades, neighborhood mediation programs have become an increasingly popular method to deal with conflicts between neighbors. In the current paper the aim is to propose and show that conflict asymmetry, the degree to which parties differ in perceptions of the level of conflict, may be important for the course and outcomes of neighborhood mediation. Design/methodology/approach -Data for testing the hypotheses were based on coding all (261) files of neighbor conflicts reported to a Dutch neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…The idea that third parties may play a role in addressing disputants' need for emotional help (Giebels & Yang, 2009) and acknowledgement (Ufkes et al, 2012) has already been suggested. However, this is the first study in the context of hierarchical labour conflicts, relating disputants' experience of anger recognition on the part of the mediator and mediation effectiveness.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The idea that third parties may play a role in addressing disputants' need for emotional help (Giebels & Yang, 2009) and acknowledgement (Ufkes et al, 2012) has already been suggested. However, this is the first study in the context of hierarchical labour conflicts, relating disputants' experience of anger recognition on the part of the mediator and mediation effectiveness.…”
Section: Discussionmentioning
confidence: 98%
“…Of all negative emotions, predominantly anger plays a crucial role (Barclay, Skarlicki, & Pugh, 2005;Jameson, Bodtker, & Jones, 2006;Van Kleef & Côté, 2007). What they need is someone who listens in an empathetic way (Druckman & Olekalns, 2008) and provides them with emotional help (Giebels & Yang, 2009) as well as acknowledgement (Ufkes, Giebels, Otten, & Van der Zee, 2012). Emotional recognition may especially be relevant in Western cultures since Dutch people, compared to Chinese people, appreciate emotional help and prefer it above relational help (Giebels & Yang, 2009).…”
Section: The Importance Of Anger Recognition In Mediationmentioning
confidence: 97%
“…It has been argued that judiciary "encouragement" to participate in the process, which is opposed to the prevailing conception of voluntary mediation, may lead the parties to mediate unwillingly. The asymmetrical nature of court-referred mediation may also lead the parties to object to the mediation process (Ufkes et al, 2012). In addition, it has been argued that under court-referred mediation, disputants (especially the plaintiffs) often refuse to compromise, resulting in a low agreements rate and only low-level satisfaction from the mediation outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Court-referred mediation is asymmetrical as one disputantthe plaintiff -wants to change the status quo, while the other -the defendant -wants to maintain it; thus, the plaintiff often practically drags the defendant into court-referred mediation. Such asymmetry may affect the mediation process and the mediation perception (Ufkes et al, 2012). The loss of the plaintiff's motivation to re-establish the relationship with the other party may also diminish the probability of reaching an agreement (Poitras, 2009).…”
Section: The Prospect Theorymentioning
confidence: 97%
“…Despite the growing interest in conflict asymmetry in the conflict literature (De Dreu, Kluwer, & Nauta, 2008;Jehn & Chatman, 2000;Ufkes, Giebels, Otten, & van der Zee, 2012), many different conceptualizations of asymmetry have been used (Giebels, Ufkes, & van Erp, 2014). For example, some studies have looked at the effects of asymmetry of roles and power between conflict parties such as the asymmetry between spouses with unequal divisions of household tasks (Kluwer, Heesink, & Van de Vliert, 2000).…”
Section: Rispensmentioning
confidence: 99%